Macromolecular organization of chicken type X collagen in vitro (The Rockefeller University Press, 1991)
The macromolecular structure of type X collagen in the matrices of primary cultures of chick hypertrophic chondrocytes was initially investigated using immunoelectron microscopy. Type X collagen was observed to assemble into a matlike structure with-in the matrix elaborated by hypertrophic chondrocytes. The process of self assembly was investigated at the molecular level using purified chick type X collagen and rotary-shadowing EM. It was shown that under neutral conditions at 34 degrees C, individual type X collagen molecules associate rapidly into multimeric clusters via their carboxy-terminal globular domains forming structures with a central nodule of carboxy- terminal domains and the triple helices radiating outwards. Prolonged incubation resulted in the formation of a regular hexagonal lattice by lateral association of the juxtaposed triple-helical domains from adjacent multimeric clusters. This extended lattice may play an important role in modifying the cartilage matrix for subsequent events occurring in endochondral bone formation.